Timing Metabolic Depression: Predicting Thermal Stress in Extreme Intertidal Environments - Tin Yan Hui; Yun-wei Dong; Guo-dong Han; Sarah L. Y. Lau; Martin C. F. Cheng; Chayanid Meepoka; Monthon Ganmanee; Gray A. Williams (My University, 2020)
AbstractAnticipatory changes in organismal responses, triggered by reliable environmental cues for future conditions, are key to species' persistence in temporally variable environments. Such responses were tested by measuring the physiological performance of a tropical high-shore oyster in tandem with the temporal predictability of environmental temperature. Heart rate of the oyster increased with environmental temperatures until body temperature reached ∼37°C, when a substantial depression occurred (∼60%) before recovery between ∼42° and 47°C, after which cardiac function collapsed. The sequential increase, depression, and recovery in cardiac performance aligned with temporal patterns in rock surface temperatures, where the risk of reaching temperatures close to the oysters' lethal limit accelerates if the rock heats up beyond ∼37°C, coinciding closely with the body temperature at which the oysters initiate metabolic depression. The increase in body temperature over a critical threshold serves as an early-warning cue to initiate anticipatory shifts in physiology and energy conservation before severe thermal stress occurs on the shore. Cross-correlating the onset of physiological mechanisms and temporal structures in environmental temperatures, therefore, reveals the potential role of reliable real-time environmental cues for future conditions in driving the evolution of anticipatory responses.
Keywords: Environmental stress; Environmental change; Physiological and biochemical adaptations